Utilizatorii colecției „Hasdeologie”: aspecte cantitative și calitative - BIVOL, Maria (BIBLIOPOLIS, 2025)
The “Hasdeologie” Collection at the B.P. Hasdeu Municipal Library preserves the cultural legacy of the Hâjdău-Hasdeu family through rare documents, literary works, scientific studies, and biographical publications. Available both physically and digitally, the collection was accessed over 4000 times between 2016-2024. Its main users include intellectuals, students, pupils, and librarians. Through exhibitions and digitization, the collection continues to make a significant impact in the academic and cultural spheres.